2016
DOI: 10.1097/md.0000000000002652
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid and Vitamins D and B12 Correlate With Homocysteine in Chinese Patients With Type-2 Diabetes Mellitus, Hypertension, or Cardiovascular Disease

Abstract: Elevated serum homocysteine has been shown to be a risk factor for hypertension, cardiovascular disease (CVD), and type-2 diabetes mellitus (T2DM).We characterized the relationships between the serum levels of homocysteine, folic acid, and vitamins D2, D3, and B12 in patients with T2DM, CVD, and hypertension in Shanghai, China. The levels of these serum biochemical markers were determined for 9311 Chinese patients (mean age: 79.50 ± 13.26 years) with T2DM (N = 839), hypertension (N = 490), or CVD (N = 7925). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 39 publications
0
36
0
1
Order By: Relevance
“…This suggests homocysteine may be decreased by processes which are upregulated following UVR exposure. Vitamin D, which is consistently inversely associated with homocysteine levels [50][51][52][53][54], may be involved in this process or may be a marker of sun-exposure, supporting this hypothesis. Increased oxidative stress following UVR exposure may also influence homocysteine levels, by promoting homocysteine auto-oxidization and the formation of homocysteine into another oxidant not detected by homocysteine assays [55].…”
Section: Discussionmentioning
confidence: 71%
“…This suggests homocysteine may be decreased by processes which are upregulated following UVR exposure. Vitamin D, which is consistently inversely associated with homocysteine levels [50][51][52][53][54], may be involved in this process or may be a marker of sun-exposure, supporting this hypothesis. Increased oxidative stress following UVR exposure may also influence homocysteine levels, by promoting homocysteine auto-oxidization and the formation of homocysteine into another oxidant not detected by homocysteine assays [55].…”
Section: Discussionmentioning
confidence: 71%
“…This genetic risk can be influenced by folate, with the highest risk at the lowest levels of folate intake . In China, the average folate intake is far below the recommended level, which means that additional folate supplementation is very necessary .…”
Section: Introductionmentioning
confidence: 99%
“…At home and abroad, the results of the study on supplementation of folic acid to reduce Hcy concentration were inconsistent (13)(14)(15) . A previous study found that more than 40 % patients with HHcy failed to reach the normal level after folic acid supplementation (16) .…”
mentioning
confidence: 99%